Unlearning eugenics : sexuality, reproduction, and disability in post-Nazi Europe - Herzog, Dagmar, 1961- (George L. Mosse series in modern European cultural and intellectual history., 2018)
Since the defeat of the Nazi Third Reich and the end of its horrific eugenics policies, battles over the politics of life, sex, and death have continued and evolved. The author documents how reproductive rights and disability rights, both latecomers to the postwar human rights canon, came to be seen as competing - with unexpected consequences. Bringing together the latest findings in Holocaust studies, the history of religion, and the history of sexuality in postwar - and now also postcommunist - Europe, this book shows how central the controversies over sexuality, reproduction, and disability have been to broader processes of secularization and religious renewal. The author also restores to the historical recorded a revelatory array of activists: Catholic and Protestant theologians who defended abortion rights in the 1960s and 1970s; historians in the 1980s and 1990s who uncovered the long-suppressed connections between the mass murder of the disabled and the Holocaust of European Jewry; feminists involved in the "cripple movement" of the 1980s; lawyers working for right-wing NGOs in the 2000s; and present-day disability advocates.